كتاب وصف أقاليم شبه الجزيرة العربية لكارستن نيبور - الحبوبي، شيماء ماجد (جامعة بغداد - مركز إحياء التراث العلمي العربي, 2024)
تناول البحث دراسة كتاب وصف أقاليم شبه الجزيرة العربية للمؤلف الدنماركي كارستن نيبور إن دراسة محتويات هذا الكتاب لها أهمية كبيرة تتجلى في انه مصدر مهم قدم لنا معلومات قيمة تتعلق بشبه الجزيرة العربية كونها منطقة مغلقة لم تكن تتوفر عنها معلومات قبل رحلة نيبور، لاسيما وانه قد وصل إلى أماكن لم تكن قد وطأتها قدم قبله، إلى جانب حصوله على نقوش ساهمت في إثراء معلوماتنا فيما بعد عن اليمن. إلى جانب النسخة الأجنبية للكتاب وجدت نسخة ألمانية وأخرى فونسية، وقد حصلت الباحثة على ترجمتين للكتاب نشرتهما دار الانتشار العربي في بيروت الأولى في عام ۲۰۰۷م، والترجمة الثانية في عام ۲۰۱۳ م، الأمر الذي دفع الباحثة ونتيجة للاختلافات في مضمون الترجمة إلى دراسة الكتاب دراسة منهجية. قسم البحث إلى ثلاث أقسام، تناول القسم الأول نبذة عن حياة مؤلف كتاب (وصف أقاليم شبه جزيرة العرب) كارستن نيبور، أما القسم الثاني فقد تضمن عرضا تاريخيا موجزا لمادة الكتاب، أما القسم الثالث فقد تضمن دراسة منهجية للكتب المترجمة عن كتاب وصف أقاليم شبه الجزيرة العربية، حيث تناول فقرات تضمنت مقدمة الكتب المترجمة، ومتن الكتب، والهوامش، ومن ثم ختمت موضوع الدراسة بالاستنتاجات وصولا إلى قائمة المحتويات. The research dealt with a study of the book Description of the Territories of the Arabian Peninsula by the Danish author Carsten Niebuhr. Studying the contents of this book is of great importance, as it is an important source that provided us with valuable information related to the Arabian Peninsula, as it is a closed region for which no information was available before Niebuhr’s journey, especially since he reached places that no foot had set foot before him, in addition to obtaining Inscriptions that contributed to enriching our later information about Yemen. In addition to the foreign version of the book, I found a German version and a French version. The researcher obtained two translations of the book published by the Arab Publishing House in Beirut, the first in 2007 AD, and the second translation in 2013 AD, which prompted the researcher, as a result of the differences in the content of the translation, to study the book systematically. The research was divided into three sections. The first section dealt with an overview of the life of the author of the book (Description of the Territories of the Arabian Peninsula), Carsten Niebuhr. The second section included a brief historical presentation of the book’s material. The third section included a systematic study of the books translated from the book Description of the Territories of the Arabian Peninsula. Arabic, where he dealt with paragraphs that included the introduction to the translated books, the body of the books, and the footnotes, and then concluded the subject of the study with conclusions leading to the list of contents.
Keywords: نيبور، كارستن، ت. 1815 م. -- الروايات الغربية -- الأحداث السياسية